Fish community composition in selected seagrass beds in Taklong Island National Marine Reserve, Nueva Valencia, Guimaras, Philippines - Navarra, Viann D. (2016.)
Seagrass beds are a valuable component of the coastal ecosystem and highly regarded for their nursery function and feeding ground for various fishes and invertebrates with important economic, ecological, and conservation values. This study determined the composition of fish community structure in selected seagrass beds within Taklong Island National Marine Reserve (TINMR) in Nueva Valencia, Guimaras and related it with the seagrass bed structure. Underwater fish visual census was conducted in December 2015 at four seagrass sites, namely Bagatnan, Calapran, Kalirohan and Piagao. Seagrass bed structure was assessed based on percent cover, blade density, shoot density, leaf blade per species, and above ground biomass through plot sampling method. A total of 945 individuals, representing 31 species from 14 fish families were recorded. There was positive correlation observed between seagrass cover and fish abundance (r = 0.890). Seagrass cover and fish abundance was highest in Bagatnan (% cover = 28.5%; n = 361), followed by Calaparan (% cover = 15.7%; n = 289), then Kalirohan (% cover = 13.3%; n = 148), and lowest in Piagao (% cover = 11.1%; n = 147). Similarly, positive correlation observed between seagrass cover and species richness (r = 0.764) and seagrass cover and density (r = 0.888). Negative correlation was observed between seagrass cover and fish diversity (r = 0.447). There were more reef-associated fish than typical residents of seagrass meadows due to the proximity of coral reef habitat to the seagrass and tidal condition during sampling. Although only a few fish species were found typically confined to seagrass, this habitat is important for its function as a food resource and nursery and feeding ground for juveniles of reef-associated species.
Research Paper -- Bachelor of Science in Public Health. University of the Philippines Visayas, Miagao, Iloilo
Keywords: Fish Community; Seagrass; Taklong Island National Marine Reserve